Answer:
<em>x = -3 and y = 0</em>
Step-by-step explanation:
<em>It would be more direct to apply elimination in this problem, rather than substitution:</em>
2x + 6y = -6 ⇒ 2x + 6y = -6 ⇒ 10x = - 30
+ 2(4x - 3y = -12) + 8x - 6y = -24
<em>Now let us solve for x through simply algebra:</em>
10x = -30,
<em>x = -3</em>
<em>Substitute this value of x into the first equation to get the value of y:</em>
2( -3 ) + 6y = -6,
-6 + 6y = -6,
6y = 0,
<em>y = 0</em>
Answer:
x=2
Step-by-step explanation:
Answer: 40.15
Step-by-step explanation: 40.15 IS LESS THEN 48.60
for 6
in a
given
slope(m)=1
point=(2,-4)=(x1,y1)
we know
equation of straight line
y-y1=m(x-x1)
y+4=1(x-2)
y+4=x-2
therefore x-y-6=0 is the required equation
substituting with ax+by+c=0 we get
a=1
b= -1
c= -6
Answer:3
Step-by-step explanation: